2015
DOI: 10.1115/1.4030514
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nonuniform Under-Rib Convection on Reactant and Liquid Water Distribution in Proton Exchange Membrane Fuel Cells

Abstract: The performance of a proton exchange membrane (PEM) fuel cell strongly depends on the nature of reactant distribution and the effectiveness of liquid water removal. In this work, three different configurations of a mixed flow distributor are studied analytically and numerically to find out the effect of nonuniform under-rib convection on reactant and liquid water distribution in the cell. In a mixed flow distributor, the rate of under-rib convection is found to be different under each rib in the same flow sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One direction is to develop the under-rib mass transport. The roles of the under-rib mass transport were previously studied [2,[12][13][14][15][16][17][18][19][20][21][22]. It was reported that for a specified mass flow rate, the under rib convection is mainly affected by different factors such as the rib width, the pressure difference between the adjacent channels, and the diffusion layer permeability [9,23].…”
Section: Introductionmentioning
confidence: 98%
“…One direction is to develop the under-rib mass transport. The roles of the under-rib mass transport were previously studied [2,[12][13][14][15][16][17][18][19][20][21][22]. It was reported that for a specified mass flow rate, the under rib convection is mainly affected by different factors such as the rib width, the pressure difference between the adjacent channels, and the diffusion layer permeability [9,23].…”
Section: Introductionmentioning
confidence: 98%